Double Atom Catalysts: Heteronuclear Transition Metal Dimer Anchored on Nitrogen‐Doped Graphene as Superior Electrocatalyst for Nitrogen Reduction Reaction. Issue 12 (2nd November 2020) - Zheng, Guokui; Li, Lei; Hao, Shaoyun; Zhang, Xingwang; Tian, Ziqi; Chen, Liang
Abstract: The electrochemical nitrogen reduction reaction (NRR) is considered as a promising alternative to the traditional Haber–Bosch process, but the development of a highly active and selective electrocatalyst remains a great challenge. In this research, density functional theory calculations are performed to screen a series of heteronuclear and homonuclear transition metal dimers anchored on nitrogen‐doped graphene (M1 M2 @N6 and M1 M1 @N6, M1, M2 = Mn, Fe, Co, Ni, Mo) for NRR. Among them, heteronuclear CoMo@N6 is screened out as the most promising electrocatalyst because of its high selectivity, activity, and stability. This work not only predicts a promising electrocatalyst candidate for NRR, but also provides a useful guideline for the rational design of heteronuclear double atom catalysts. Abstract : CoMo@N6 is screened out from a series of heteronuclear and homonuclear transition metal dimers anchored on nitrogen‐doped graphene for electrochemical nitrogen reduction reaction, owing to its high activity, selectivity, thermal, and electrochemical stability. The barrier of the potential determining step of CoMo@N6 is lower than or comparable to most single atom catalysts in experiments.